Review of mobile short message service security issues and techniques towards the solution - Medani, A.; Gani, Abdullah; Zakaria, O.; Zaidan, A.A.; Zaidan, B.B. (2011)
The short message service (SMS) is one of the highly used and well-tried mobile services with global availability within all GSM networks. The existing SMS is limited to the transmission of secure plain text between different mobile phone subscribers. SMS does not have any built-in procedure to authenticate the text and offer security for the text transmitted as data, because most of the applications for mobile devices are designed and developed without taking security into consideration. This paper details an overview of the current SMS security aspects and concerns during the SMS transmission. It also chronologically presents the existing mechanisms used to protect the SMS with the goal to provide useful advices for further research. In addition, the security and efficiency of these mechanisms are analysed, considering the limitation on the mobile devices and the security requirements. Finally it suggests the SMS security future direction for generating extra research topics.